Embarazo múltiple: diagnóstico y manejo ultrasonográfico: Embarazo Múltiple - Muñoz , Hernán; Urzúa, Soledad; Valenzuela, Marco; Parra, Lorena; Neumann, Paola (Revista Hospital Clínico Universidad de Chile, 1998)
Resumen no disponible